Laboratory investigation of the rediffusion of contaminants originated from the aquiclude - Poczok, Noémi; Székely, István; Madarász, Tamás (International Journal of Engineering and Management Sciences, 2019)
Many organic pollutants are released into the soil and thus into the groundwater due to anthropogenic effects (a chain of harmful human activities). Layers with low permeability (e.g. clay) play an important role in blocking the path of these contamintants. However, due to their sorption and diffusion properties, such aquiclude layers can also serve as long-term sources of contamination. Once the layer is contaminated, it is already very difficult to recultivate, and there is a potential for the pollutant to spread to higher permeability layers by slow diffusion processes. This phenomenon is defined as a so-called rediffusion process, in which contaminants are retransferred from the aquiclude to the layer with higher permeability. The purpose of this study is to demonstrate the possibility of modeling this rediffusion process in a laboratory scale and to quantify the effect of influencing parameters on pollutant transport.